Pembatasan Kegiatan Keagamaan oleh Pemerintah Daerah: Konstitusionalitas dan Prinsip Negara Hukum: Restrictions on Religious Activities by Local Governments: A Study on Constitutionality and the Rule of Law Principle - Rifa'i, Iman Jalaludin; Azizah, Naili (Constitution Journal, 2025)
Decentralization under Law Number 23 of 2014 grants broad authority to local governments in managing social and religious affairs. However, practices such as the prohibition of Ahmadiyya Jamaah’s Jalsah Salanah by certain regional governments raise tensions between freedom of religion and the rule of law. This study aims to evaluate the legality and legitimacy of such restrictions using John Rawls’ theory of justice, particularly the principles of basic liberties and the difference principle. A normative juridical method is employed, with statutory, case-based, and conceptual approaches. The findings reveal that many local regulations lack a national legal basis, fail the proportionality test, and discriminate against minority groups without social compensation, thereby conflicting with Rawlsian principles. The study concludes that Rawlsian justice principles must be integrated into local legislative processes, judicial review mechanisms strengthened, and inclusive deliberative forums implemented to ensure regional autonomy aligns with constitutional supremacy. Practically, this research offers an evaluative framework for local policymakers and serves as a normative reference for the Supreme Court and Constitutional Court in reviewing potentially discriminatory local regulations. Abstrak Desentralisasi melalui Undang-Undang Nomor 23 Tahun 2014 memberikan kewenangan luas kepada pemerintah daerah dalam urusan sosial dan keagamaan. Namun, praktik pembatasan ibadah oleh beberapa Pemda, seperti pelarangan Jalsah Salanah Jamaah Ahmadiyah, menimbulkan konflik antara kebebasan beragama dan prinsip negara hukum. Penelitian ini bertujuan mengevaluasi legalitas dan legitimasi pembatasan tersebut dengan teori keadilan John Rawls, khususnya prinsip kebebasan dasar dan difference principle. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan, kasus, dan konseptual. Hasil penelitian menunjukkan bahwa sejumlah kebijakan daerah tidak berlandaskan hukum nasional, tidak proporsional, serta merugikan kelompok minoritas secara diskriminatif. Kesimpulannya, diperlukan integrasi prinsip keadilan Rawlsian dalam legislasi daerah, penguatan judicial review, dan forum deliberatif yang inklusif agar otonomi daerah tidak melanggar supremasi konstitusi. Penelitian ini berkontribusi dalam menyediakan kerangka evaluatif bagi pemerintah daerah dan menjadi rujukan normatif bagi Mahkamah Agung dan Mahkamah Konstitusi dalam menilai keabsahan peraturan daerah yang potensial melanggar kebebasan beragama.